Mathematics Connection Ability and Self Regulated Learning of Junior High School Students Trough Problem-Based Learning Approach - Nendi Rohaendi (IKIP Siliwangi, 2020)
This article aims to examine the mathematical connection skills of students who learn using the Problem Based Learning approach and Selft Regulated Learning compared to those who use ordinary learning. This research is using the experimental method. The population in this study were eighth-grade students of MTs Al-Hikmah 02 Talegong Garut district 2018/2019 academic year with a sample of the study were eighth-grade students of MTs Al-Hikmah 02 Talegong consisting of VIIB classes as a control class and VIIA as experimental classes taken randomly. The instrument used in this study was a mathematical connection ability test in the form of a description of 5 questions, as well as the scale of learning independence. Data were analyzed using the IBM SPSS Statistic 1.7 for windows program. From this study, the following results were obtained: (1) Increased mathematical connection ability of students with mathematical learning using the PBL approach better than those who used ordinary learning. (2) Learning independence of students who use the PBL approach is better than students who use ordinary learning. (3) Implementation of learning steps using the PBL approach can develop mathematical connection skills and student learning independence. (4) the difficulties experienced by students in solving the problems of mathematical connection ability are found in indicators that understand or connect the relationship between mathematics and other sciences outside mathematics.